Methodological approaches to the study of reverse martensitic transformation in metastable austenitic steels. Issue 1 (January 2021) - Panov, D O; Smirnov, A I; Simonov, Y N; Stepanov, N D; Salishchev, G A
Abstract: Methodological aspects of the high-resolution dilatometry analysis of the reverse α→γ-transformation in cold-worked metastable austenitic steel Fe-0.07C-18.7Cr-9.2Ni-0.6Ti-1.1Mn-0.4Si (wt.%) were considered. It was shown that the reverse α→γ-transformation occurs in the temperature range from AS =520 °C to AF =920 °C. Two consecutive stages corresponding to shear and diffusion transformations were revealed. An abnormal increase in the sample length of the program steel during the reverse α→γ-transformation was found. The recrystallization process also developed during austenitization and was accompanied by a decrease in length of the specimen.